Determination Of Sun Protective Factor (SPF) Values In N-Hexane, Ethyl Acetate, And Water Fractions Of Ethanol Extract Of Tamarind Eggplant (Solanum Lasiocarpum Dunal.) Peel With UV-VIS Spectrophotometry Method - Natalia Riska Angelinda; Septian Maulid Wicahyo; Alfina Nurrahman (International Journal of Health Engineering and Technology, 2026)
Excessive UV exposure causes skin damage, so natural sunscreen alternatives are needed. This experimental descriptive study aims to identify and measure the Sun Protection Factor (SPF) value of ethanol extract and n-hexane, ethyl acetate, and water fractions from Solanum lasiocarpum Dunal fruit peel in vitro using UV-Vis spectrophotometry. The population of the entire skin simplicia from Tanjung Hulu, Pontianak; a sample of 500 g of powder (mesh 40) was extracted and fractionated. Instruments include a Thermo Scientific UV-Vis spectrophotometer (290-320 nm), rotary evaporator, TLC plate; SPF was calculated using the Mansur equation and Lambert-Beer validation linear regression. The results showed the highest SPF of ethyl acetate fraction (36.97 at 500 ppm, high category), while the ethanol extract (9.32), n-hexane (6.71), and water (6.76) were low. Phytochemical screening was positive for alkaloids, terpenoids, phenolics, and flavonoids. In conclusion, the ethyl acetate fraction has optimal potential for the development of sunscreen cosmetics.